The Role of Library Volunteers in Conducting Library Promotion of the Bank Indonesia Representative Office of Sumatra Utara - Hidayat, Tengku Riyan; Achiriah, Achiriah (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study intends to clarify the function and accomplishment of library volunteers in attracting patrons to the Indonesian Bank's North Sumatra representative office library. This study uses a qualitative case study methodology at the Library of the Bank Indonesia Representative Office in North Sumatra. The research findings take the form of information about the contribution and effectiveness of library volunteers in promoting the library of the Bank Indonesia representative office in North Sumatra. Library volunteers collected the information. Techniques for gathering data include observation, interviewing, and documenting. At the same time, data analysis is accomplished by data reduction, presentation, inference, and verification. According to the study's findings, a volunteer librarian at the Bank Indonesia North Sumatra representative office assisted the librarian in carrying out outreach efforts to promote the public to the library. Additionally, library volunteers participate in all the activities the library undertakes and participate in library promotion efforts. Several marketing initiatives have been implemented, such as POCABI, the Library Competition, North Sumatra's creative works, webinars, podcasts, book exhibitions, book reviews, etc. Due to the rapid growth of social media and the enthusiasm of millennials, library volunteers also promote the library online. Young, talented library volunteers also run and design the libraries on social media platforms like Instagram, YouTube, and TikTok. Additionally, they frequently share information about reading interests and literacy with the material.